Love in Transit: The Plasticity of Love in Mohsin Hamid’s Exit West and Sharon Bala’s The Boat People - Ghosal, Abhisek (SARE: Southeast Asian Review of English, 2019)
This paper is an analysis of the plasticity of love and its appropriation as an effective strategy for those in power to deal with the refugee crisis. It contends that a contextualization of love is needed to point to some of the ways in which love’s plasticity is employed to combat refugee uprisings. Through an analysis of Mohsin Hamid’s Exit West (2017) and Sharon Bala’s The Boat People (2018), this paper demonstrates how the ruling governments, of different contexts, either overtly or covertly, resort to politicizing love in order to defuse tensions between refugees and “insiders”.